2019
DOI: 10.1002/prs.12101
|View full text |Cite
|
Sign up to set email alerts
|

Explosion mitigation of methane‐air mixture in combined application of inert gas and ABC dry powders in a closed compartment

Abstract: The explosion is one of the most serious safety incidents occurring in the application of the gas methane in industrial process. The new developments in attenuating the destruction and environmental hazard of this explosion are conducted using the combined inert gas and ABC dry powder. The explosive characteristic parameters including flame configuration, velocity of flame propagation, explosion pressure, and pressure rising rate are quantified and revealed. The difference of explosion mitigation effect of ord… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…Via a vertical combustion tube, Zhao et al [10] examined the deflagration of methane, coal dust, and ABC dry powder. Through experimentation, Li et al [11] analyzed the CO 2 and ultrafine ABC dry powder explosion suppression method. Through experimental quantification, Song et al [12] investigated the impact of sedimentary rock powder volume on explosion overpressure, temperature, and flame velocity.…”
Section: Introductionmentioning
confidence: 99%
“…Via a vertical combustion tube, Zhao et al [10] examined the deflagration of methane, coal dust, and ABC dry powder. Through experimentation, Li et al [11] analyzed the CO 2 and ultrafine ABC dry powder explosion suppression method. Through experimental quantification, Song et al [12] investigated the impact of sedimentary rock powder volume on explosion overpressure, temperature, and flame velocity.…”
Section: Introductionmentioning
confidence: 99%
“…Powders, inorganic salts, and fluorinated alkanes are other common chemical antiknocks. Scholars frequently undertake methane explosion suppression studies with a mixture of several chemicals in order to increase the efficacy of explosion suppression 9 . Ingram et al 10 investigated the use of nitrogen and an ultrafine water mist to control hydrogen explosions in a synergistic manner.…”
Section: Introductionmentioning
confidence: 99%
“…Scholars frequently undertake methane explosion suppression studies with a mixture of several chemicals in order to increase the efficacy of explosion suppression. 9 Ingram et al 10 investigated the use of nitrogen and an ultrafine water mist to control hydrogen explosions in a synergistic manner. Their findings revealed that nitrogen and ultrafine water mist might have a substantial impact on the pace of flame propagation and pressure of a hydrogen explosion.…”
Section: Introductionmentioning
confidence: 99%
“…The results showed that an inhibitor composed of NaHCO 3 (BC) powder/inert gas had better inhibition performance in comparison to an inhibitor composed of NH 4 H 2 PO 4 (ABC) powder/inert gas. Li et al 23 used the combination of an inert gas and ABC powder to suppress methane explosion. On the basis of the flame morphology, flame propagation velocity, explosion pressure, and booster rate, the explosion suppression mechanism was explained by the physical and chemical aspects.…”
Section: Introductionmentioning
confidence: 99%